2012
DOI: 10.3892/ijmm.2012.944
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of oxidative modification in endothelial colony-forming cells treated by hydrogen peroxide

Abstract: Abstract. Endothelial progenitor cells (EPCs) which circulate in the peripheral blood and reside in blood vessels are proven to promote the repair of damaged endothelium and improve the function of endothelial cells after vascular injury. Recently, EPCs have been extensively studied as risk biomarkers and a potential therapeutic tool for cardiovascular disease. It is known that oxidative stress is one of the most important pathogenetic factors impairing endothelial function. During the repair process after end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Various cell activities, including migration, morphological changes and polarity formation are regulated by actin filament dynamics, including actin filament disassembly, severing and reorganization ( 47 , 48 ). Previous studies have demonstrated that actin dysfunction results in impaired ECFC functions, including tubule formation ( 22 , 49 ). Annexin A2 is crucial in actin cytoskeletal rearrangements by binding the regions of free-barbed ends ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various cell activities, including migration, morphological changes and polarity formation are regulated by actin filament dynamics, including actin filament disassembly, severing and reorganization ( 47 , 48 ). Previous studies have demonstrated that actin dysfunction results in impaired ECFC functions, including tubule formation ( 22 , 49 ). Annexin A2 is crucial in actin cytoskeletal rearrangements by binding the regions of free-barbed ends ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…The tube-forming capacity of ECFCs was measured using a Matrigel assay, as previously described ( 22 , 23 ). Briefly, following treatment, the ECFCs were trypsinized and seeded at a density of 3×10 4 cells/cm 2 onto 96-well plates, which were pre-coated with 50 µ l Matrigel™ (BD Biosciences), and incubated for 24 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%